DETERMINASI KEPUASAN HEDGING DENGAN INSTRUMEN DERIVATIF KEUANGAN - Hilda Utami; Sriyanto Sriyanto; Intan Purbasari (Tirtayasa Ekonomika, 2018)
This study conducted to see the effect of the company’s firm size, leverage, growth opportunity and profitability on the decision of hedging with derivative instruments on manufacturing companies listed on the Indonesian Stock Exchange  period 2011-2016. Sample in this study uses 34 companies by using purposive sampling method. This study uses a quantitative approach and data used secondary data. The analytical method used is logistic regression. The results shower that the variable firm size and growth opportunity have a significant positive effect on hedging decision making. The variable leverage and profitability did not influence hedging decision in Indonesian manufacturing companies. This study show that the higher value of firm size will increase the probabilitiy of using hedging activity in manufacturing companies in Indonesia.